The socio economic impact of Dao Federation Small Farmers Multi Purpose Cooperative in the life of its beneficiaries in Dao, Capiz - Dordas, Ma. Susan F.
This is basically a descriptive study of the Cooperative "The Socio-economic impact of Dao Federation of small farmers Multi Purpose Cooperative in the lives of its beneficiaries in Dao, Capiz. This study aims to know how the cooperative have socially and economically affected the lives of its beneficiaries in Dao, Capiz. Specifically it wishes to answer the following questions: 1) is there a significant effect in the lives of the respondents before and after the organization of Dao Federation of small Farmers Multi Purpose Cooperative. 2) What are the effect of Dao Federation of Small farmers Multi Purpose cooperative in the lives of its beneficiaries as to economic status, level of living, level of aspiration, and level of community participation. The study will be conducted at Dao Federation of small Farmers Multi purpose Cooperatives in Dao, Capiz. It will used the Descriptive Method of Investigation based on the questionnaires undertaken by the researchers. This study was limited to only 51 beneficiaries of the Dao Federation of small Farmers Multi Purpose cooperative, in Dao Capiz, before and after its implementation. The main concern of this study were limited to the socio-economic impact of the Cooperative movements on its beneficiaries particularly on : a) Economic status b)level of living c) level of aspiration d) level of community participation